ANALISIS KETERLAKSANAAN PEMBELAJARAN JARAK JAUH MATA PELAJARAN MATEMATIKA DI KELAS TINGGI SEKOLAH DASAR PADA MASA PANDEMI COVID-19 - Dyoty Auliya Vilda Ghasya; Asmayani Salimi; Rio Pranata (Program Studi Pendidikan Matematika, Universitas Bina Bangsa Getsempena, 2021)
The research aims to describe the learning planning of Mathematics subjects that have been made by teachers in grade IV, V and VI elementary schools, describing the pattern of implementation of distance learning in mathematics subjects grade IV, V and VI elementary school, describing the difficulty of teachers in carrying out distance learning in mathematics subjects grade IV, V and VI elementary school , describe the difficulties of grade IV, V and VI elementary school students in following distance learning in Mathematics subjects, describe the advantages of the implementation pattern of distance learning in mathematics grade IV, V and VI elementary school, and describe the opinions of parents or guardians of students on distance learning of Mathematics subjects grade IV, V and VI elementary school during the COVID-19 pandemic. This study uses qualitative research approach with exploration study type. The result of this study is distance learning in mathematics subjects grade VI, V and VI elementary schools there are conducted online and mixed. The implementation of distance learning in mathematics subjects grade VI, V and VI received a variety of responses from teachers, students and parents or guardians. Abstrak Penelitian bertujuan untuk mendeskripsikan perencanaan pembelajaran mata pelajaran Matematika yang telah di buat oleh guru pada kelas IV, V dan VI sekolah dasar, mendeskripsikan pola pelaksanaan pembelajaran jarak jauh mata pelajaran Matematika kelas IV, V dan VI sekolah dasar, mendeskripsikan kesulitan guru dalam melaksanakan pembelajaran jarak jauh pada mata pelajaran Matematika kelas IV, V dan VI sekolah dasar, mendeskripsikan kesulitan siswa kelas IV, V dan VI sekolah dasar dalam mengikuti pembelajaran jarak jauh pada mata pelajaran Matematika, mendeskripsikan kelebihan pola pelaksanaan pembelajaran jarak jauh mata pelajaran Matematika kelas IV, V dan VI sekolah dasar, dan mendeskripsikan pendapat orang tua atau wali murid terhadap pembelajaran jarak jauh mata pelajaran Matematika kelas IV, V dan VI sekolah dasar pada masa pandemi COVID-19. Penelitian ini menggunakan pendekatan penelitian kualitatif dengan jenis studi eksplorasi. Adapun hasil dari penelitian ini adalah pembelajaran jarak jauh pada mata pelajaran matematika kelas VI, V dan VI sekolah dasar ada yang dilaksanakan secara online maupun campuran. Pelaksanaan pembelajaran jarak jauh pada mata pelajaran matematika kelas VI, V dan VI mendapatkan berbagai respon dari guru, siswa dan orang tua atau wali murid. Kata Kunci: Pembelajaran Jarak Jauh, Matematika, Kelas Tinggi Sekolah Dasar